Design of a covalently immobilized alpha-glucosidase and glucose oxidase biosensor for detection of maltose and kinetic study for maltose hydrolysis - Tan Chia Shin (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
A hybrid sol gel modified nanobiosensor has been developed to determine quantitty of maltose generated by hydrolysis of starch in the presence of a-amylase. The biosensor was developed by covalent immobilization of a-glucosidase and glicose oxidase anzyme on sol gel modified electrode with ferrocene via carbodiimide reaction. The presence of amine groups provided by APTMOS in sol gel controlled the covalent bonding sites for enzyme. The immobilization conditions such as amount of enzymes, immobilization time and pH in working buffer was studied by using Response Surface Methodology (RSM) through Central Composite Design (CCD) of Design Expert software.